2004
DOI: 10.1021/es0350740
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Acetic Acid and Landfill Leachates for the Leaching of Pb(II), Cd(II), As(V), and Cr(VI) from Cementitious Wastes

Abstract: The Toxicity Characteristic Leaching Procedure (TCLP) has been widely used to characterize the suitability of solid wastes for disposal in landfills. However, the widespread application of this test for the assessment of wastes disposed in different landfill types is often questionable. This paper investigates the leaching profiles of cement-stabilized heavy metal ions, namely, Pb (II), Cd (II), As(V), and Cr(VI), using acetic acid and leachates from municipal and nonputrescible Australian landfill sites. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 21 publications
(22 reference statements)
1
28
0
Order By: Relevance
“…The leached concentration of Cd from PC2_C10 and SS2_C10 specimens was higher than that of non-carbonated PC2_C0 and SS2_C0 specimens. The increased concentration of Cd may be due to a decrease of pH in carbonated specimens (Fleischer et al 1974;Halim et al 2004). In previous studies, solubility of Cd increased with the lowering of pH due to carbonation (Fleischer et al 1974;Halim et al 2004).…”
Section: Heavy Metal Leaching Characteristics Of Carbonated Porous Comentioning
confidence: 99%
“…The leached concentration of Cd from PC2_C10 and SS2_C10 specimens was higher than that of non-carbonated PC2_C0 and SS2_C0 specimens. The increased concentration of Cd may be due to a decrease of pH in carbonated specimens (Fleischer et al 1974;Halim et al 2004). In previous studies, solubility of Cd increased with the lowering of pH due to carbonation (Fleischer et al 1974;Halim et al 2004).…”
Section: Heavy Metal Leaching Characteristics Of Carbonated Porous Comentioning
confidence: 99%
“…Because of the dependence on a single leaching result, the TCLP has been scrutinized due to its widespread application for evaluating and regulating waste (Kosson, van der Sloot, Sanchez, & Garrabrants, 2002). Halim et al (2004) found that TCLP underestimated the leaching of Pb and Cd from cementitious wastes, compared to MSW leachates. They postulated that this was due to complexation of the elements with organic materials in the MSW leachates to form soluble metal-organic complexes, increasing the mobility of these ions.…”
mentioning
confidence: 99%
“…These compounds have been frequently used in compatibility studies of CCLs (Foreman and Daniel 1986;Bowders and Daniel 1987;Olgun and Yildiz 2010;Benson et al 2015) to represent different types of chemicals found in waste disposal units: neutral polar industrial solvents (methanol), waste oils and some industrial solvents (n-heptane), and recalcitrant hazardous chlorinated organic chemicals (TCE). Acetic acid was used to represent the organic acids fraction in waste landfill leachates (Ö man and Hynning 1993), and it is also used as leaching agent in the US EPA TCLP procedure (Halim et al 2004). Ca 2?…”
Section: Red Mudmentioning
confidence: 99%